Identification of thermostable glycogen branching enzyme from Geobacillus sp. Geo5 by genome mining - Mohtar, Nur Syazwani (2013)
Glycogen branching enzyme (EC 2.4.1.18) has increasing demand from food and beverages processing industries. This enzyme, which catalyses the formation of α-1,6-glycosidic branch points in glycogen structure, is used to enhance nutritional value and quality of food and beverages. To be applicable in industries, enzymes that are stable and active at high temperature are much desired. A thermophilic bacterium, Geobacillus sp. Geo5, was isolated from Sungai Klah Hot Springs at97°C and therefore it was postulated that this bacterium species would produce thermostable glycogen branching enzyme that is active at high temperature. The objectives of this research are to identify the branching enzyme gene (glgB) of Geobacillus sp. Geo5, to produce the enzyme using Escherichia coli and to characterise the biochemical properties of the enzyme. Using genome data mining, the nucleotide sequence of glgB was fished out from Geobacillus sp. Geo5 genome sequence provided by Malaysia Genome Institute. The size of the gene is 2013 bp and the theoretical molecular weight of the protein is 78.43 kDa. The gene sequence was then used to predict the three dimensional structure of the enzyme using an online software, I-TASSER. The percentage sequence identity of the template (Mycobacterium tuberculosis H37RV; PDB ID: 3K1D) in the threading aligned region with the Geobacillus sp. Geo5 sequence was only 45%. Subsequently, glgB from Geobacillus sp. Geo5 was isolated using polymerase chain reaction (PCR). To study the enzyme, the gene was cloned into pET102/D-TOPO® vector by PCR cloning and overexpressed in BL21 Star TM (DE3) E. coli. The expression of active enzyme was the highest when the expression was induced with 0.75 mM of IPTG, at 30°C for 8 hours. The recombinant protein was also expressed together with bacteriocin release protein to secrete the protein into E. coli culture medium. The study shown that induction with 5 ng/mL of mitomycin C for 8 hour was enough to secrete the recombinant protein to extracellular environment (34.1 U/mL) although not entirely since 43.0 U/mL of the activity was still in the cell. Therefore, the intracellular expression system was chosen for further studies on the enzyme. The recombinant protein from intracellular expression was then purified by affinity chromatography using HisTrap HP column with the recovery of 84%. The purified enzyme was used to study the effect of temperature and pH on enzyme activity and stability, and the inhibitory effect by metal ion on enzyme activity. This thermostable glycogen branching enzyme was found to be most active at 55°C and the half-life at 60°C and 70°C was 24 hours and 5 hours, respectively. The enzyme was stable at pH 5 to pH 9 and the optimum pH for enzyme activity was at pH 6. Metal ions, Mn2+, Zn2+, Cu2+, Fe2+ and Ca2+ seem to inhibit the activity of this enzyme. Mg2+ however does not affect the enzyme activity. From this research, a thermostable glycogen branching enzyme was successfully isolated from Geobacillus sp. Geo5 by genome mining together with molecular biology technique. The stability of this enzyme would be very practical for industrial applications especially in carbohydrates processing such as nutraceutical, food and beverages industries.